2021
DOI: 10.1016/j.ejpn.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic variability and natural history of NARS2 associated disease

Abstract: Introduction:The phenotypic variability of NARS2 associated disease is vast, yet not thoroughly explored. We present the phenotypic and genetic features of 2 siblings with early-onset mitochondrial encephalopathy due to pathogenic variant in NARS2, along with the results from a systematic literature review. Aims: To better delineate the phenotypic variability and natural history of NARS2 associated disease. Methods: The clinical and radiological phenotype, along with the results from the morphological and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…The pathogenic NARS2 variant (p.S264C) maps in the catalytic domain of the mitochondrial asparaginyl-tRNA synthase protein, which catalyzes the binding of asparagine to its cognate mt-tRNA ( Bonnefond et al, 2005 ). Several studies reported NARS2 variants in LS patients ( Simon et al, 2015 ; Sofou et al, 2015 ; Mizuguchi et al, 2017 ; Lee et al, 2020 ; Sofou et al, 2021 ). More relevant is the sensorineural hearing impairment, as a hallmark of NARS2 -associated LS phenotype, which is consistent with the proband’s symptoms ( Sofou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic NARS2 variant (p.S264C) maps in the catalytic domain of the mitochondrial asparaginyl-tRNA synthase protein, which catalyzes the binding of asparagine to its cognate mt-tRNA ( Bonnefond et al, 2005 ). Several studies reported NARS2 variants in LS patients ( Simon et al, 2015 ; Sofou et al, 2015 ; Mizuguchi et al, 2017 ; Lee et al, 2020 ; Sofou et al, 2021 ). More relevant is the sensorineural hearing impairment, as a hallmark of NARS2 -associated LS phenotype, which is consistent with the proband’s symptoms ( Sofou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 truncation variant in POLG was identified (Wolf et al, 2009). Variants in PARS2, CARS2, GABRB2, FARS2, and NARS2 were also reported in Alpers' syndrome patients (Sofou et al, 2015;Walker et al, 2016;Samanta et al, 2018;Sofou et al, 2021). All the variations were consistent with the autosomal recessive inheritance pattern, except for that in GABRB2.…”
Section: Results Mutation Outcomesmentioning
confidence: 62%
“…Next-generation sequencing has significantly broadened our understanding of the genetic causes of mitochondrial disease (Jin et al, 2019;Li et al, 2019;Shen and Shi, 2019). In recent years, an increasing number of genes have been related to Alpers' syndrome, many pathogenic mutations in the mitochondrial aminoacyl-tRNA synthetases (mt-aaRSs), such as FARS2, CARS2, NARS2, and PARS2, etc, are a novel cause of mitochondrial translation disorder, leading to Alpers' syndrome (Elo et al, 2012;Sofou et al, 2015;Walker et al, 2016;Samanta et al, 2018;Sofou et al, 2021). This study demonstrated the pathogenic mechanism of gene variants resulting in the loss of receptor function (Nishikawa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LS is characterized by psychomotor regression with progressive loss of mental and movement abilities and may result in fatal encephalopathy [14,15]. The disorder could be associated with mutations in more than 75 genes that have been identified in both the nuclear and mitochondrial genome; about 20% of LS cases are caused by mtDNA mutations [16][17][18]. Point mutations at m.8993T>G or the less severe m.8993T>C in MT-ATP6 gene in the complex V are the most frequent LS-associated mtDNA changes.…”
Section: Introductionmentioning
confidence: 99%